Exploring the barriers and facilitators of psychological safety in primary care teams: a qualitative study - Ridhaa Remtulla; Arwa Hagana; Nour Houbby; Kajal Ruparell; Nivaran Aojula; Anannya Menon; Santhosh G. Thavarajasingam; Edgar Meyer (BMC, 2021)
Abstract Background Psychological safety is the concept by which individuals feel comfortable expressing themselves in a work environment, without fear of embarrassment or criticism from others. Psychological safety in healthcare is associated with improved patient safety outcomes, enhanced physician engagement and fostering a creative learning environment. Therefore, it is important to establish the key levers which can act as facilitators or barriers to establishing psychological safety. Existing literature on psychological safety in healthcare teams has focused on secondary care, primarily from an individual profession perspective. In light of the increased focus on multidisciplinary work in primary care and the need for team-based studies, given that psychological safety is a team-based construct, this study sought to investigate the facilitators and barriers to psychological safety in primary care multidisciplinary teams. Methods A mono-method qualitative research design was chosen for this study. Healthcare professionals from four primary care teams (n = 20) were recruited using snowball sampling. Data collection was through semi-structured interviews. Thematic analysis was used to generate findings. Results Three meta themes surfaced: shared beliefs, facilitators and barriers to psychological safety. The shared beliefs offered insights into the teams' background functioning, providing important context to the facilitators and barriers of psychological safety specific to each team. Four barriers to psychological safety were identified: hierarchy, perceived lack of knowledge, personality and authoritarian leadership. Eight facilitators surfaced: leader and leader inclusiveness, open culture, vocal personality, support in silos, boundary spanner, chairing meetings, strong interpersonal relationships and small groups. Conclusion This study emphasises that factors influencing psychological safety can be individualistic, team-based or organisational. Although previous literature has largely focused on the role of leaders in promoting psychological safety, safe environments can be created by all team members. Members can facilitate psychological safety in instances where positive leadership behaviours are lacking - for example, strengthening interpersonal relationships, finding support in silos or rotating the chairperson in team meetings. It is anticipated that these findings will encourage practices to reflect on their team dynamics and adopt strategies to ensure every member's voice is heard.